Blade Antenna Design for UHF Applications - Belen, Aysu; Partal, Hakan P.; Ordek, Sezgin; Belen, Mehmet A. (IEEE, 2018)
The importance of today's wireless communication systems are ever increasing due to the high demand. With the development and common usage of the next generation wireless communication devices the need of high rate data transfer is increased. Herein design and measurement of a low cost high gain blade antenna for 600-3000 MHz UHF band is studied. In order to achieve a wide band high gain radiation characteristic a wide band range impedance matching over the operation band is done. The proposed design allows usage of a single antenna model over the wide operation frequency band instead of multi antenna models. Thus, with this model it is possible to reduce both the size of communication system and its cost. In this proposed blade antenna design, by creating gaps on the antennas surface a wide range impedance matching is achieved due to the change of surface current distribution. As it can be observed from the measurement results the proposed antenna's return loss characteristic is less than -6db, and has a gain characteristic of 4.5-6.2 dB over the operation band.
Keywords: Blade antenna; UHF; wide band; directional antenna; Engineering; Telecommunications